UMUMIY O’RTA TA’LIM MAKTABLARIDA “SCRATCH” DASTURINI O’RGATUVCHI MOBIL ILOVADAN FOYDALANISH - Z.M.Rahimberdiyev; Sh.F.Reyimbayev; T.T.Xudaybergenov (Лучшие интеллектуальные исследования, 2024)
Abstract: This article covers the basics of programming in general secondary schools, a mobile application that teaches Scratch, as well as learning other types of programming languages from this application, the process of using mobile applications in the educational process, and mobile the organization of the application is mentioned.